Formation of financial real estate risks and spatial interactions: Evidence from 35 cities in China - Fengyun Liu; Honghao Ren; Chuanzhe Liu; Dejun Tan (Journal of Risk and Financial Management, 2022)
The real estate prices in urban China have been soaring sharply since the commercialization reform of the housing market in 1998, but have suffered from downward pressure recently. In addition to the peculiarities of the state-owned land system, newly built houses dominate market across the vast territories of China, and this study of China will further the understanding of the financial real estate risks. Based on theoretical analyses, a spatial Durbin model is adopted to evaluate the financial real estate risks based on various sectors' participation in the real estate market, because it can overcome the biased results brought about by the omission of possible spatial dependence. The results show the following: (1) the four sectors' participation in the real estate market promotes the rise of real estate prices in the both local and other cities with spatial contagion effects, while the most important factors are different across regions; (2) the real estate price fluctuations, the local government's land revenue, the bank credit provided to the real estate industry, the demand in the local city, and the real estate developers' investments in other cities increase the local financial real estate risks, and there are strong spatial diffusion effects among the cities. This study sheds light on the roles of the various sectors' participation in promoting the financial real estate risk as well as their spatial interactions from both theoretical and empirical aspects. Particularly, the different roles of local governments and real estate developers in China should be highlighted. The rules on the sector and spatial levels suggest that government policy should take the different features of various sectors and regions and spatial connections into account.
Keywords: R31; P34; 650; China; financial risk; real estate price; regional difference; spatial diffusion